(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Nomadism is a lifestyle of people who do not live permanently in one place, but constantly move cyclically or periodically from one place to another. The study seeks to investigate the effect of their migration on agricultural production in Lere Local Government Area of Kaduna State Nigeria. The study is guided by objective of this research is to examine the socio-economic characteristics of fulani migration in the study area, also to examine the causes and effect of Fulani migration in the study area and the challenges faced by Fulani migration in the study area. The study adopted survey research design. Fifty (50) nomads were randomly selected from five communities in the study area. A structured questionnaire was used to elicit data from the respondents. The data gathered were subjected to analysis using frequencies and simple percentages. The result revealed that majority of the respondents strongly agreed that the rural banditry and cattle rustling can cause the migration of nomadic Fulani with 43(86%) while only 7(14%) of respondents strongly disagreed with statement among others. It was recommended that the relevant agencies of government and the civil society should work towards reviewing existing and developing new mechanisms for the monitoring and control of Nomadic Fulani migration across the Lere area due to low agricultural production.